Pengaruh Kualitas Produk, Citra Merek, Dan Celebrity Endorser Terhadap Minat Beli Pada Produk Ms Glow (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2018) - Shabilla Nur Azizah Fauzy; Nurhidayah Nurhidayah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of product quality, brand image, and celebrity endorser on buying interest in the Ms Glow Beauty, a case study of FEB UNISMA students class 2018. the population in this study were students of FEB UNISMA. This research includes explanator research with a quantitative approach. The sampling used was purposive samping, with a total sample of 97 respondent data collection techiniques using questionnaires via google from. The population in this study was FEB UNISMA students class 2018. the result of this study product quality and brand image partially affect buying interest but of the celebrity endorser variable it has no effect on buying interest because consumers have been familiar with Ms Glow Beauty product beforse the celebrity endorse. Keywords: Product Quality, Brand Image, Celebrity Endorser, And Buying Interest